A Validation Study of the Psychometric Properties of the Other As Shamer Scale–2. (April 2017) - Saggino, Aristide; Carlucci, Leonardo; Sergi, Maria Rita; D'Ambrosio, Ines; Fairfield, Beth; Cera, Nicoletta; Balsamo, Michela
External shame is associated to social and emotional difficulties, which are predictors of psychological disorders. The aim of the present study was to investigate the psychometric properties of the shorter Italian version of the Other As Shamer Scale (OAS-2), a measure of external shame. Confirmatory factor analysis was used in a sample of 612 (54.2% male) Italian undergraduate students. Evidence for this model provided support for the assumption that the one-factor model was similar across the gender groups. The Italian OAS-2 fully replicated the one-factor structure of the original OAS. Cronbach's alpha index, as well as test–retest stability provided satisfactory results. The OAS-2 showed good convergent and divergent validity, being highly correlated with measures of internal shame, trait anxiety, and depression. The OAS-2 can be considered a useful instrument for measuring external shame when time constraints impede the use of the 18-item OAS. Implications of the results are discussed and recommendations for future work with the scale are made.